KIAI DESA IN DEFENDING PANCASILA: - Zaki Mubarok (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), 2019)
This article discusses the models of Islamic moderation implemented by kiai desa in Tegal Regency which have a significant role in defending Pancasila from the threat of anti-Pancasila movements. For kiai desa, keeping the country which is based on Pancasila is an implementation of the faith to God which should be implemented in the real act in the middle of traditional society, not only doctrinal. This article states two models of moderation done by kiai desa in defending Pancasila, i.e. delegation and mediatisation. Through the delegation model, kiai desa supplies the values of moderation to hissantri or colleagues using political line, whether the Regent or DPRD to defend Pancasila. Meanwhile, by doing mediatisation, kiai desa spreads the values of moderation in communal Qur'an reading activities through social media or radio station. When defending Pancasila from the threat of anti-Pancasila movements, kiai desa often faces authoritarianism and populism toward them. Authoritarianism of Islam is done by the 'new santri' who try to delegitimize the knowledge possessed by kiai desa in defending Pancasila. Populism tries to popularize kiai desa as the enemies of Islam itself because defending Pancasila which is not 'Islam'. Populism also struggles for sharia country by defending people who support it. This characterization is built by the politicians using the idioms of religion in the middle of this democratic country.   Key words: kiai desa, models of Islamic moderation, Pancasila